UCFM as the forerunner in the field of Laboratory Animal Science in Sri Lanka (Journal of Laboratory Animal Science, 2024)
Animals have been models for humans since the dawn  of medicine as per the first medical handbook ‘Corpus  Hippocraticum’ (around 400 B.C). In an era where no  anaesthetic agents were identified, live animals such as dogs,  pigs and monkeys were the subjects for vivisections to study  human anatomy. Reverend Stephen Hales (1677–1761)  inserted a brass pipe into a major blood vessel in the neck of a  live horse through which a glass tube was sent and introduced  the concept of blood pressure to the scientific fraternity (van  Zutphen, 2001; Lewis, 1994; Felts, 1977). Similar to these,  different animals have been the models for development of  many fields of medicine especially for the benefit of humans.  The objective of this article is to describe the role played by  the Faculty of Medicine, University of Colombo (UCFM) as  the forerunner in laboratory animal science in Sri Lanka to  facilitate laboratory animal use in medical education, research,  ethics and laboratory animal science education.
Keywords: museum; Although